Determinants of Contingent Convertible Bond Coupon Rates of Banks: An Empirical Analysis - Michael Sigmund; Kevin Zimmermann (Oesterreichische Nationalbank (OeNB), 2021)
In this paper, we analyze the determinants of coupon rates of contingent convertible bonds (CoCos). We construct a data set of additional Tier 1 (AT1) CoCos issued by banks in the European Economic Area between 2014 and 2020. Following elements of the standard asset pricing model with additional factors motivated by the arbitrage pricing theory, we empirically test whether di erent conversion types as well as several other factors determine the coupon rate besides the yields of other portfolios. We find that CoCo coupon rates are sensitive to risk variables at the instrument-, bank-, country- and market-level. In contrast to theoretical pricing models, we cannot confirm the expected price premium for the conversion type permanent-principal-write-down (PPWD) compared to conversion-to-equity (CE) and temporary-principal-write-down (TPWD). Our findings suggest that there is risk-shifting incentive induced by CoCo investors as well as a selection process into di erent conversion types, with the majority of PPWD CoCos being issued in Switzerland and most of the CE CoCos being issued in Great Britain and Spain.
Keywords: 330; Contingent convertible bonds; asset pricing; banks; risk factors